Răspuns :
a= 3⁶⁰³-3⁶⁰²-3⁶⁰⁰=3⁶⁰⁰*(3³-3²-1)=3⁶⁰⁰(27-9-1)=3⁶⁰⁰* 17
b= 2⁶⁰⁵-2⁶⁰⁴+2⁶⁰⁰= 2⁶⁰⁰*(2⁵-2⁴+1)=2⁶⁰⁰*(32-16+1)=2⁶⁰⁰*17
a > b
b= 2⁶⁰⁵-2⁶⁰⁴+2⁶⁰⁰= 2⁶⁰⁰*(2⁵-2⁴+1)=2⁶⁰⁰*(32-16+1)=2⁶⁰⁰*17
a > b
3 la puterea 600 x ( 3 la puterea 3 - 3 la puterea 2 - 1 ) .... 2 la puterea 600 x ( 2 la puterea 5 - 2 la puterea 4 + 1 )
3 la puterea 600 x 17 .... 2 la puterea 600 x 17
3 la puterea 600 x 17 mai mare decat 2 la puterea 600 x 17
a mai mare decat b
3 la puterea 600 x 17 .... 2 la puterea 600 x 17
3 la puterea 600 x 17 mai mare decat 2 la puterea 600 x 17
a mai mare decat b